Dimple Creation Surgery - Lee, Kimberly J.; Cutri, Raffaello M. (Facial Plastic Surgery, 2025)
Dimple creation surgery, or dimpleplasty, recreates the dynamic cheek indentations found in approximately 30% of faces. This review highlights current evidence and provides surgical insights for predictable, natural outcomes.Since 1962, successive refinements of the technique have focused on smaller incisions and precise dermomuscular fixation.Awareness of zygomaticus major variants, orbicularis oculi bands, Stenson's duct, and buccal branches of the facial nerve underpins safe practice.Bipolar cautery may assist with hemostasis.Healthy adults with realistic expectations benefit most. Those with keloid tendency warrant caution.A 5-mm intraoral incision, selective muscle fenestration, and dermomuscular plication produce an immediate dimple that softens with healing.Brief oral antibiotics support recovery.AI-assisted 3D smile simulation is being conducted and refined to boost dimple creation precision and predictability.With surgical precision and careful patient selection, dimpleplasty remains a low-risk procedure that can deliver high patient satisfaction.
Keywords: dimples; dimple creation; dimpleplasty; zygomaticus major; cheek aesthetics; intraoral surgery